Propagation of short-period gravity waves at high-latitudes during the MaCWAVE winter campaign - K. Nielsen; M. J. Taylor; P.-D. Pautet; D. C. Fritts; N. Mitchell; C. Beldon; B. P. Williams; W. Singer; F. J. Schmidlin; R. A. Goldberg (Annales Geophysicae, 2006)
As part of the MaCWAVE (Mountain and Convective Waves Ascending Vertically) winter campaign an all-sky monochromatic CCD imager has been used to investigate the properties of short-period mesospheric gravity waves at high northern latitudes. Sequential measurements of several nightglow emissions were made from Esrange, Sweden, during a limited period from 27–31January 2003. Coincident wind measurements over the altitude range (~80–100 km) using two meteor radar systems located at Esrange and Andenes have been used to perform a novel investigation of the intrinsic properties of five distinct wave events observed during this period. Additional lidar and MSIS model temperature data have been used to investigate their nature (i.e. freely propagating or ducted). Four of these extensive wave events were found to be freely propagating with potential source regions to the north of Scandinavia. No evidence was found for strong orographic forcing by short-period waves in the airglow emission layers. The fifth event was most unusual exhibiting an extensive, but much smaller and variable wavelength pattern that appeared to be embedded in the background wind field. Coincident wind measurements indicated the presence of a strong shear suggesting this event was probably due to a large-scale Kelvin-Helmholtz instability.